Ready player one a novel - Cline, Ernest; Wheaton, Wil. (New York : Random House Audio, 2011)
It's the year 2044 and Wade Watts escapes his grim surroundings by spending his waking hours jacked into the OASIS--a sprawling virtual utopia that lets you be anything you want to be. OASIS creator James Halliday has hidden a series of fiendish puzzles that will yield massive fortune and Wade stumbles upon the first puzzle.
Compact discs.
Read by Wil Wheaton.
Keywords: Regression (Civilization) -- Fiction; Virtual reality -- Fiction; Utopias -- Fiction; Puzzles -- Fiction; Fantasy fiction